Distribution of edin in Staphylococcus aureus isolated from diabetic foot ulcers. (23rd November 2012) - Messad, N.; Landraud, L.; Canivet, B.; Lina, G.; Richard, J.‐L.; Sotto, A.; Lavigne, J.‐P.; Lemichez, E.; ,; Raoult, D.
Abstract Staphylococcus aureus is both a common colonizer of human skin and the most frequently isolated pathogen in diabetes foot infections (DFIs). The spread of DFI to soft tissue and bony structures is a major causal factor for lower‐limb amputation. It is therefore of great importance to differentiate colonizing from infecting strains of S. aureus. Epidermal cell differentiation inhibitors known as EDIN and EDIN‐like factors, a group of toxins targeting RhoA master regulator of the actin cytoskeleton, may confer virulence properties on S. aureus. In this study, for the first time, analysis of S. aureus strains, recovered in DFIs at an initial stage and during the follow‐up, showed that 71.4% of edin‐positive strains were associated with moderate‐to‐severe infections (grades 3 and 4 of the IDSA/IWGDF classification) compared with 28.6% of edin‐positive strains associated with low‐grade infections. Most of these strains were edin‐B positive (86.7%) and belonged to CC25/28‐MSSA (n = 10). One edin‐B‐positive ST152‐MSSA strain was negative for the two highly prevalent predictive markers of infecting strains (lukDE and hlgv). Collectively, this points towards the edin‐B encoding gene as a bonafide subsidiary predictive risk marker of DFI.